Peran Akuntansi Lingkungan dalam Optimalisasi Green Tax: Sebuah Systematic Literature Review - Nasution; Adi Supriyadi; Ade Imam Muttaqien Halim (Sigma: Journal of Economic and Business, 2025)
This study aims to analyze the relationship between Environmental Accounting (EA), GreenTax (GT) policies, and the role of regulatory frameworks in supporting corporate sustainabilitypractices. Using a Systematic Literature Review approach on relevant studies, this researchmaps how the quality of environmental reporting and measurement serves as a fundamentalbasis for the effectiveness of environmentally oriented fiscal policies. The findings indicate thatEA provides the accurate data required for determining tax rates and designing Green Taxmechanisms, while the effectiveness of GT is strongly influenced by a firm’s ability to manageand utilize environmental information. Additionally, the strength of institutional and regulatoryframeworks significantly affects compliance levels and the overall impact of green taxationacross countries. The results highlight that EA and GT are mutually reinforcing, withregulatory governance acting as a supporting element that ensures both operate optimally.This study implies that improving EA quality, enhancing regulatory consistency, andstrengthening corporate commitment to environmental disclosure are key factors in increasingthe effectiveness of sustainability-based fiscal policies.